Central Kalimantan Dayak Creative Dance Training as an Effort to Maintain Cultural Existence among Students at SDN 7 Pahandut, Palangka Raya City - Astuti, Andi Arie; Mayangsari, Marrisa Aulia; Maulana, Muhammad Ahsin; Samosir, Hendro T.G; Darmawan, Cahyo Wahyu (Abdi Masyarakat, 2024)
This service activity provides an experience of local culture, especially dance at Central Kalimantan, SDN 7 Pahandut in Central Kalimantan Dayak dance creations. Community service activities provide knowledge about the diversity of dances that exist in Central Kalimantan and increase students' ability to perform Central Kalimantan Dayak creative dance movements. For teachers, it is hoped that this activity will make it easier to determine the material to be taught as well as become a reference in the future learning process. Based on the activities carried out by the PKM Team during these 3 days, several results were obtained, including: Dance training was more popular with female students than male students. This is because students think that dancing is an activity or action that is generally carried out by women. So male students feel embarrassed to dance. In this case, the PKM Team provides training based on student interests and without any coercion on students. The initial training process is an introduction to the types of Central Kalimantan Dayak dance and creative dance that will be taught. This introduction is nailing to the training participants. From the coercion process, the result was that students began to get to know Central Kalimantan Dayak dance. This can be seen from the body movements of students who start to sculpt little by little. The dance demonstration given uses simple movements which are traditional Central Kalimantan Dayak dance movements that are modified and combine several traditional Central Kalimantan Dayak dance movements which are packaged according to elementary school children's dance movements so that they can be easily imitated by students.